Self-Evaluative and Other-Directed Emotional and Behavioral Responses to Gossip About the Self - Martinescu, Elena; Janssen, Onne; Nijstad, Bernard A. (Frontiers in Psychology, 2019)
Gossip, or informal talk about others who are not present, is omnipresent in daily interactions. As such, people who are targeted are likely to hear some gossip about themselves, which may have profound implications for their well-being. We investigated the emotions and behavioral intentions of people who hear performance-related gossip about themselves. Based on the affective events theory, we predicted that gossip incidents have strong emotional consequences for their targets and that these emotional responses trigger different behaviors. Two scenario studies (N1 = 226, Mage = 21.76; N2 = 204, Mage = 34.11) and a critical incident study (N = 240, Mage = 37.04) compared targets' responses to positive and negative gossip. Whereas, targets of positive gossip experienced positive self-conscious emotions (e.g., pride), targets of negative gossip experienced negative self-conscious emotions (e.g., guilt), especially when they had low core self-evaluations. In turn, these negative self-conscious emotions predicted repair intentions. Positive gossip also led to positive other-directed emotions (e.g., liking), which predicted intentions to affiliate with the gossiper. Negative gossip, however, also generated other-directed negative emotions (e.g., anger), especially for targets with high reputational concerns, which in turn predicted retaliation intentions against the gossiper. This pattern of emotional reactions to self-relevant gossip was found to be unique and different from emotional reactions to self-relevant feedback. These results show that gossip has self-evaluative and other-directed emotional consequences, which predict how people intend to behaviorally react after hearing gossip about themselves.